The Application of Cold Compression to Reduce Pain Scale in Postoperative Fracture Patients at Kartini Regional General Hospital of Karanganyar - Wardhani, Amelia Ayu Kusuma; Imamah, Ida Nur; Sugito (Al-Hijrah Indonesia, 2025)
Background: Fractures are a primary global health concern, with an estimated incidence of 440 million cases worldwide. The most commonly affected areas are the lower extremities (67%) and upper extremities (32%). Preliminary data from Kartini Karanganyar Regional General Hospital (RSUD) revealed a rising trend in fracture cases over the past three years: 309 patients in 2022, 428 in 2023, and 435 in 2024. Objective: This study aimed to evaluate the effectiveness of cold compression therapy in reducing pain levels among postoperative fracture patients at Kartini Karanganyar Hospital. Method: A case study design was employed for 2 respondent, with pain intensity measured before and after intervention using the Visual Analog Scale (VAS). Cold compresses were applied for 20 minutes over 2 days. Results: Both respondents showed reduced pain scale scores following the cold compress intervention. Conclusion: Applying cold compresses effectively reduces postoperative pain in fracture patients, supporting its use as a non-pharmacological pain management strategy.